Evaluation of biofuel from the torrefaction of Malaysian food waste - Rahsya Nur Udzaifa, Abdul Rahman; Ruwaida, Abdul Rasid; Yong, Yung Sheng; Mazni, Ismail (Elsevier Ltd, 2024)
The alarming issues related to the depletion of conventional fossil-based fuel resources have sparked interest in the search for alternative resources. Being a developing country facing tremendous growth, Malaysia is generating large amounts of food waste (FW). In this paper, an investigation of the potential of FW conversion to solid, coal-like fuel is carried out through torrefaction. The torrefaction process was carried out at temperatures between 260 and 320 °C and residence times of 15 to 45 min. The results showed that a higher torrefaction temperature leads to an increase in mass loss of the initial solid FW, which is also observed with increasing residence time. The loss of solid mass, nevertheless, increased the higher heating value (HHV) of the torrefied FW. A significant improvement was also observed in the volatile matter (VM) and moisture content (MC) of torrefied FW, which both decreased, while the carbon (C) content was increased. This suggests the improvement in the fuel properties of FW and its potential as a renewable energy source.